2015
DOI: 10.1590/s0102-6720201500s100016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Nutritional Aspects in Obese Women During the First Year After Roux-en-Y Gastric Bypass

Abstract: Background: Clinic care for morbid obesity is not very effective. Bariatric surgery is being considered the best way of intervention for this kind of obesity. Aim : Evaluate the clinical and nutritional evolution during the first year of obese women submitted to Roux-en-Y gastric bypass. Method : Retrospective series non-concurrent with 61 women. The variables were weight, BMI, weight loss percentage, loss of excessive weight percentage, waist circumference, hip circumference, lipid profile, daily use of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…In this study, was observed a curve for %LEW similar to those seen in the literature 5 , 11 , 24 , 25 and also that the different sizes of intestinal loops did not influence this variable. Two retrospective studies by Christou 6 and Feng 12 found no statistical difference in relation to weight loss and %LEW in a follow-up of 60 months and 12 months, respectively, when comparing different sizes of intestinal loops.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, was observed a curve for %LEW similar to those seen in the literature 5 , 11 , 24 , 25 and also that the different sizes of intestinal loops did not influence this variable. Two retrospective studies by Christou 6 and Feng 12 found no statistical difference in relation to weight loss and %LEW in a follow-up of 60 months and 12 months, respectively, when comparing different sizes of intestinal loops.…”
Section: Discussionsupporting
confidence: 88%
“…It is important that the serum iron levels be monitored regularly. Some studies suggest that vitamin C supplementation can help in iron deficiency for assisting in the absorption process 6 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The disease has reached epidemic proportions worldwide and results from the interaction of genes, environment, lifestyle and emotional factors. 1 The prevalence of obesity has rapidly increased in Brazil. The country ranks 5 th in the world ranking, amounting to approximately 60 million overweight and 22 million obese individuals.…”
Section: Introductionmentioning
confidence: 99%